Identification of appropriate reference genes for local immune-related studies in Morada Nova sheep infected with Haemonchus contortus - Barbosa Toscano, Joao Henrique [UNESP]; Lopes, Louyse Gabrielli; Giraldelo, Luciana Aparecida; Silva, Matheus Henrique da; Okino, Cintia Hiromi; Souza Chagas, Ana Carolina de (Springer, 2018)
Due to the great economic impact of Haemonchus contortus on sheep farming, there is an increasing number of studies addressing host resistance against this nematode, including identification of directly related immune mechanisms. In this context, relative gene expression by RT-qPCR have been largely used, due to its rapidity, high sensitivity, specificity, and reproducibility. Although, appropriate reference gene selection is crucial for accurate interpretation of results. In this study, five reference genes (GAPDH, G6PDH, YWHAZ, ACTB, and B2M) were tested for expression stability in abomasum (fundic and pyloric regions) and abomasal lymph nodes of Morada Nova sheep classified as resistant (n = 5) or susceptible (n = 5) to H. contortus infection in a flock of 151 animals. GAPDH combined with YWHAZ were selected as reference genes for abomasal fundic region and abomasal lymph nodes, whereas YWHAZ was the most stable gene for abomasal pyloric region. These genes presented the lowest intra- and inter-group variations and, consequently, highest stability. In contrast, expression of G6PDH was the least stable in all tissues. The impact of reference gene selection was demonstrated by relative quantification of a pro-inflammatory cytokine (TNF alpha) in abomasal fundic region. Significant differences in TNF alpha expression levels between resistant and susceptible groups were only observed when the most stable genes (GAPDH combined with YWHAZ) or GAPDH were used as reference genes, whereas no significant differences were observed when other tested reference genes were used. It was demonstrated that normalization of expression data using inappropriate reference genes may significantly influence interpretation results.
Keywords: Reference gene; RT-qPCR; Haemonchus contortus; Host resistance; Morada Nova breed; Sheep